Exploring whether wireless emergency alerts can help impede the spread of Covid‐19. (30th September 2021) - Bean, Hamilton; Grevstad, Nels; Meyer, Abigail; Koutsoukos, Alex
Abstract: Officials worldwide have sought ways to effectively use mobile technology to communicate health information to help thwart the spread of Covid‐19. This study offers a preliminary exploration of whether state‐level ( N = 6) and local‐level ( N = 53) wireless emergency alert (WEA) messages might contribute to impeding the spread of Covid‐19 in the United States. The study compares changes in reported rates of infections and deaths between states and localities that issued WEA messages in March and April of 2020 with states that did not. Small sample sizes and differences in the rates of Covid‐19 spread prohibit robust statistical analysis and detection of clear effect sizes, but estimated effects are generally in the right direction. Combining statistical analysis with preliminary categorization of both WEA message content and social media themes suggests that a positive effect from WEA messages cannot be ruled out.